Advances in turbulent mixing techniques to study microsecond protein folding reactions - Kathuria, Sagar V. (2013)
Recent experimental and computational advances in the protein folding arena have shown that the readout of the one-dimensional sequence information into three-dimensional structure begins within the first few microseconds of folding. The initiation of refolding reactions has been achieved by several means, including temperature jumps, flash photolysis, pressure jumps and rapid mixing methods. One of the most commonly used means of initiating refolding of chemically-denatured proteins is by turbulent flow mixing with refolding dilution buffer, where greater than 99% mixing efficiency has been achieved within 10’s of microseconds. Successful interfacing of turbulent flow mixers with complementary detection methods, including time-resolved Fluorescence Spectroscopy (trFL), Förster Resonance Energy Transfer (FRET), Circular Dichroism (CD), Small-Angle X-ray Scattering (SAXS), Hydrogen Exchange (HX) followed by Mass Spectrometry (MS) and Nuclear Magnetic Resonance Spectroscopy (NMR), Infrared Spectroscopy (IR), and Fourier Transform IR Spectroscopy (FTIR), has made this technique very attractive for monitoring various aspects of structure formation during folding. Although continuous-flow (CF) mixing devices interfaced with trFL detection have a dead time of only 30 µs, burst-phases have been detected in this time scale during folding of peptides and of large proteins (e.g., CheY and TIM barrels). Furthermore, a major limitation of CF mixing technique has been the requirement of large quantities of sample. In this brief communication, we will discuss the recent flurry of activity in micromachining and microfluidics, guided by computational simulations, that are likely to lead to dramatic improvements in time resolution and sample consumption for CF mixers over the next few years.